The Status of Undergraduate Translation Programs at Yemeni Universities in Light of Academic Accreditation Standards: Perspectives of Faculty Members and Heads of Translation Programs - Yahya, Malikah Abdulmalik A.; Al-Shamiri, Abdul-Kawi Hizam M.; Moqbel, Marwan Saeed Saif (University of Science and Technology, Sana’a, 2023)
The development of translation studies since the 1970s has led to its gradual change from a mere sub-discipline of applied linguistics and comparative literature to an independent discipline in its own right. This shift has resulted in a proliferation of translation programs at various European and Arab universities. As a result of this rapid development, it has become imperative for those universities to improve their academic programs in line with Academic Accreditation Standards (AASs). Yemeni universities, which trod a similar path to that already taken by other regional and international universities, are no exception. Thus, this study aimed at investigating the status of the undergraduate translation programs at Yemeni universities in light of AASs with a view to identifying whether these programs meet these standards from the perspectives of faculty members and heads of translation programs. The study adopted the quantitative approach to collect data from 204 faculty members and heads at four public and fourteen private Yemeni universities through a 5-point Likert scale questionnaire. The study revealed that the degree of availability of the AASs is low. It also indicated that there are statistically significant differences in the means of respondents’ responses according to the variable of academic position.
Keywords: Translation Studies; Translation Programs; Academic Accreditation Standards; Faculty Members; Yemeni Universities